The effects of BMD in lactation diets on sow and litter performance - Richert, B.T.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty-five multiparous sows were used in a performance trial to evaluate the use of BMD® (bacitracin methylene disalicylate) on sow and litter performance during lactation in a herd with no previously documented history of Clostridium perfringens type C or D. Between day 96 and 100 of gestation, sows were allotted to one of two dietary treatments, either a diet containing 250 g/ton of BMD or the control diet with no antibiotic. Sows were fed the experimental diets until weaning (approx. 20 d). Litters were equalized to approximately 10 pigs per sow within 48 hrs postfarrowing. Piglets were transferred only within treatment. Piglets on sows fed the BMD treatment had a reduced incidence of diarrhea (P=.10); however, the antibiotic had no effect on sow or litter performance.
Keywords: Swine; Bacitracin; Sow; Lactation; Performance